2000
DOI: 10.1111/j.1741-3729.2000.00097.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Stress Among Grandparents Raising Their Grandchildren*

Abstract: This cross-sectional study of 129 grandparents raising their grandchildren examined the extent to which social supports are related to the grandparents' stress (psychological anxiety). A hierarchical regression analysis, with variables entered in blocks, revealed that contextual factors, stressors related to caregiving, and lack of supports accounted for 35% of the variance. Younger grandparents, grandchildren with psychological and physical problems, and low family cohesion were associated with stress. Implic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
101
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(105 citation statements)
references
References 40 publications
2
101
1
1
Order By: Relevance
“…Sands and Goldberg-Glen, (2000) found that the most common reasons grandparents cared for grandchildren were substance abuse (71%), child neglect (60%), parent inability to care for child (60%), psychological problem (56%), financial problem (50%), and child abandonment (45%). Typically, it is assumed that grandparents care for grandchildren due to the death of a parent, incarceration, mental health, or health conditions related HIV or AIDS.…”
Section: Gaps In Literature and Need For Further Studymentioning
confidence: 98%
“…Sands and Goldberg-Glen, (2000) found that the most common reasons grandparents cared for grandchildren were substance abuse (71%), child neglect (60%), parent inability to care for child (60%), psychological problem (56%), financial problem (50%), and child abandonment (45%). Typically, it is assumed that grandparents care for grandchildren due to the death of a parent, incarceration, mental health, or health conditions related HIV or AIDS.…”
Section: Gaps In Literature and Need For Further Studymentioning
confidence: 98%
“…Grandparents with formal and informal social connections were less apt to experience psychological stress (Musil & Ahmad, 2002;Sands & Goldberg-Glen, 2000).…”
Section: Statement Of the Problemmentioning
confidence: 98%
“…Diminishing social welfare afforded to families (Iceland & Kim, 2001) and increased proportions of single parent families (Cooksey, Menaghan, & Jekielek, 1997) account in part for a growing need for the care services of grandparents. Teen pregnancy, parental substance abuse, imprisonment, mental and/or physical illness, death, or abuse and neglect of their children may result in grandparents assuming primary responsibility for their grandchildren (Sands & Goldberg-Glen, 2000). Such traumatic circumstances may result in these grandchildren experiencing unique emotional, psychological, and/or physical needs.…”
Section: Grandparents As Parents Againmentioning
confidence: 99%
“…Younger grandparents, who are still experiencing demands from the workplace as well as from their caregiving responsibilities, are apt to experience more depression and psychological anxiety Sands & Goldberg-Glen, 2000). A lack of available support is another key factor contributing to the stress of grandparent caregivers.…”
Section: Grandparents As Parents Againmentioning
confidence: 99%
See 1 more Smart Citation